A survey of weeds associated to irrigation canals and adjacent inundated rice fields at Finca El Cerrito, Guanacaste, Costa Rica. - Rojas, Manuel (2016)
A weed survey was conducted on irrigation canals and neighboring inundated rice fields, at Finca El Cerrito, Liberia, Guanacaste, Costa Rica. Sampling was performed on two growing seasons contrasting in weather conditions (rainy and dry) during 1992. Each surveying point was subdivided in five habitats (levee, internal slope, external slope, bottom of canal, and neighboring rice field). Plant species, percent cover and phenological stage were recorded at each habitat. In addition, for each species the next parameters were estimated: Frecuency-Cover Index (IFC), and Relative Participation Index (IPR). IPR at the family level was also calculated. 131 species during the dry season, and 144 species during the rainy season were recorded, showing that there is a significant plant diversity associated to these irrigation canals. The levee showed the greatest amount of plant species, while crop fields the least. Poaceae was the most important family, followed by Cyperaceae, based on IPR. Echinochloa colonum showed high IFC values and appeared in all habitats; this species together with others such as Oryza rufipogon, O. latifolia, Cyperus iria, and several broadleaf weeds are carefully controlled in rice fields, but reproduce heavily on irrigation canals, and shed their seeds in irrigation water, thus reinfesting commercial fields.